Divergent Estimates of Forest Photosynthetic Phenology Using Structural and Physiological Vegetation Indices. Issue 18 (18th September 2020) - Yin, Gaofei; Verger, Aleixandre; Filella, Iolanda; Descals, Adrià; Peñuelas, Josep
Abstract: The accurate estimation of photosynthetic phenology using vegetation indices (VIs) is important for measuring the interannual variation of atmospheric CO2 concentrations, but the relative performances of structural and physiological VIs remain unclear. We found that structural VIs (normalized difference VI, enhanced VI, and near‐infrared reflectance of vegetation) were suitable for estimating the start of the photosynthetically active season in deciduous broadleaf forests using gross primary production measured by FLUXNET as a benchmark, and a physiological VI (chlorophyll/carotenoid index) was better at identifying the end of the photosynthetically active season for deciduous broadleaf forests and both the start and end of season for evergreen needleleaf forests. The divergent performances were rooted in the combined control of structural and physiological regulations of carbon uptake by plants. Most existing studies of photosynthetic phenology have been based on structural VIs, so we suggest revisiting the dynamics of photosynthetic phenology using physiological VIs, which has significant implications on global plant phenology and carbon uptake studies. Plain Language Summary: The uptake of photosynthetic carbon by forests is strongly seasonal, which can be characterized by photosynthetic phenology, e.g., the start and end of the photosynthetically active season (SOS and EOS, respectively). Satellite vegetation indices (VIs) can detect photosynthesis in canopies either structurally or physiologically. Clarifying the convergence or divergence of the performance of structural and physiological VIs is therefore crucial. This study compared the capacity of three structural VIs and one physiological VI for estimating SOS and EOS. Their performances were jointly controlled by structural and physiological regulations of carbon uptake by plants. The structural and physiological controls for deciduous broadleaf forests (DBFs) were nearly synchronous during green‐up, and canopy structural changes were visible, so structural VIs were reliable for estimating SOS. Canopies, however, change slowly in evergreen needleleaf forests (ENFs) throughout the year and in DBFs during autumn, and the capacity to take up carbon is mainly limited by physiological stress, so physiological VIs outperformed structural VIs. Our study highlights the unique advantage of physiological VIs for estimating photosynthetic phenology. These findings constitute a step toward improving our understanding of the roles of the structural and physiological regulations of the dynamics of terrestrial carbon. Key Points: Structural and physiological regulations of plant carbon uptake determine forest photosynthetic phenology Structural vegetation indices successfully identified the start of season for deciduous forests Physiological vegetation indices tracked the best evergreen forest photosynthetic phenology and the end of season for deciduous forests